Recent Advances in CNS P2X7 Physiology and Pharmacology: Focus on Neuropsychiatric Disorders - Bhattacharya, Anindya (Frontiers in Pharmacology, 2018)
The ATP-gated P2X7 ion channel is an abundant microglial protein in the CNS that plays an important pathological role in executing ATP-driven danger signal transduction. Emerging data has generated scientific interest and excitement around targeting the P2X7 ion channel as a potential drug target for CNS disorders. Over the past years, a wealth of data has been published on CNS P2X7 biology, in particular the role of P2X7 in microglial cells, and in-vivo effects of brain-penetrant P2X7 antagonists. Likewise, significant progress has been made around the medicinal chemistry of CNS P2X7 ligands, both as antagonists for in-vivo target validation in models of CNS diseases, to identification of 2 clinical compounds (JNJ-54175446 & JNJ-55308942) and finally, discovery of P2X7 PET ligands. This review is an attempt to bring together the current understanding of P2X7 in the CNS with a focus on P2X7 as a drug target in neuropsychiatric disorders.